2006
DOI: 10.4067/s0717-95022006000500015
|View full text |Cite
|
Sign up to set email alerts
|

Biometría de las Arterias Comunicantes Posteriores y Cerebrales Posteriores en su Segmento Precomunicante (P1) en el Círculo Arterial del Cerebro (Willis)

Abstract: Biometría de la arterias comunicantes posteriores y cerebrales posteriores en su segmento precomunicante(P1) en el círculo arterial del cerebro (Willis).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
1
0
3
Order By: Relevance
“…Following, our results also coincide with Quijano & García, who reported that the A1, P1 and PCoA calibers were higher on the left side. All the same reported by Mandiola et al (2007), who also studied CAC of Chilean corpses, found similarities in the lengths of component A1, however, there are differences with Mandiola et al (2006), who reported that the caliber of P1 was greater on the right side, while the caliber of the PCoA did not present differences (Table IV). Although there is a tendency finding vessels on the left side with shorter length and greater caliber, it is complex to establish that this factor is determinant in the development of ischemic disorders, however, when in the right side, present smaller caliber vessels can be considered the existence of high resistance blood flow may influence the ability of these vessels to deliver collateral flows in ischemic events.…”
Section: Discussionmentioning
confidence: 54%
“…Following, our results also coincide with Quijano & García, who reported that the A1, P1 and PCoA calibers were higher on the left side. All the same reported by Mandiola et al (2007), who also studied CAC of Chilean corpses, found similarities in the lengths of component A1, however, there are differences with Mandiola et al (2006), who reported that the caliber of P1 was greater on the right side, while the caliber of the PCoA did not present differences (Table IV). Although there is a tendency finding vessels on the left side with shorter length and greater caliber, it is complex to establish that this factor is determinant in the development of ischemic disorders, however, when in the right side, present smaller caliber vessels can be considered the existence of high resistance blood flow may influence the ability of these vessels to deliver collateral flows in ischemic events.…”
Section: Discussionmentioning
confidence: 54%
“…Para Bugnicourt et al, la ausencia de las ACoP unilateral o bilateralmente, referidas como círculo arterial de la base posteriormente incompleto, lo han asociado, de acuerdo a sus hallazgos clínicos, a un factor de riesgo en el padecimiento de migraña. No hay datos de los autores mencionados que relacionen datos biométricos con bioantropológicos, como lo han señalado Mandiola et al (2005Mandiola et al ( , 2006.…”
Section: Resultsunclassified
“…En trabajos previos hemos hecho notar, que son escasas las investigaciones que asocian características morfológicas vasculares encefálicas con caracteres bioantropológicos (Mandiola et al, 2005(Mandiola et al, , 2006 Estos factores nos han llevado a revisar y analizar las características biométricas de las arterias comunicantes anterior y posterior (ACoA y ACoP, como componentes de la estructura del círculo arterial cerebral, intentando además, asociar sus características con mediciones bioantropológicas, de las cuales obtuvimos los índices cefálicos.…”
Section: Introductionunclassified
“…A pesar de su relevancia anatomoclínica, existen pocos trabajos en la literatura relacionados con el tema. Autores como Mandiola et al (1995aMandiola et al ( , 1995bMandiola et al ( , 1995cMandiola et al ( , 1996aMandiola et al ( , 1996bMandiola et al ( , 1996cMandiola et al ( , 1997Mandiola et al ( , 2006, han descrito una amplia variabilidad anatómica de las arterias cerebrales cuando se considera lado, sexo e índice cefálico.…”
Section: Introductionunclassified